METHOD OF "ZARANDAS" TO DETECT THE PRESENCE OF ADULTS OF WHITE WORM OF THE POTATO, Premnotrypes vorax IN THE GROUND - CALVACHE-GUERRERO, HUGO (Revista Colombiana de Entomología, 1979)
The South American potato white worm, or Andean weevil, Premnotrypes vorax (Hustache) (Coleoptera: Curculionidae) is the most important entomological problem in this crop. In its larval stage, it makes deep, sinuous, tunnels in the tubers, decreasing the quality of them. It is difficult to detect adults in the field since they look very much like small clods. For this reason, it is.difficult to carry out studies on the ecology, the distribution, and the population dynamics of this insect. Therefore, present reco¬mendations for its control are still peer. To solve these problems, studies have been carried out on different possibilities, with the aim to establish a method that permits rapid and reliable detection of the adult. As a result of this research, the method of "sieving" has been de¬veloped. This method consists of a set of sieves that separates soil particles from the adults. The remaining of this sieving are soaked in water, in order to dissolve the clods; with a fine sieve the adults of P. vorax can be sieved out, to¬gether with some organic deb.is.